Dynamic Modeling and Simulation of a Cyclic Towing System for Underwater Vehicles - Xinhao Luo; Shiping He (Applied Sciences)
The cyclic towing system for underwater vehicles presented in this paper is a platform, featuring high efficiency and flexibility that is specifically designed for hydrodynamic experiments with underwater vehicles in an experimental water tank. To study the dynamic characteristics of the cyclic towing system, this paper employs the Lagrange equations of the second kind to model the key components of the system, including the underwater vehicle, towing wheel, guiding wheel, tensioning device, and cable. The model calculates the system’s stiffness, damping, mass, and fluid resistance equations, while the overall dynamic model of the system is numerically solved using the Runge–Kutta method. The validity of this model was verified by comparing and analyzing the simulation results with those from the commercial software ADAMS. Finally, this paper discusses the effects of different operating conditions, such as input torque and tensioning force, on the system’s operation. The research findings can provide theoretical support for engineering applications of cyclic towing systems.